Abu Talib, peace be upon him, the Sponsor of the Believers, the Supporter and the Sacrifice - Hussein, أ Prof. Dr. Mahdi Oreibi; Oreibi, Lect. Dr. Mohamed Hassan (Thi Qar Arts Journal, 2022)
This research deals with the biography of Abu Talib, may God bless him and grant him peace, the uncle of the Messenger Muhammad, may God bless him and grant him peace, and his most important heroic stances in supporting the Messenger, may God bless him and grant him peace, and believing in his prayers and his Messenger. prophecy, and how he protected everyone who converted to Islam, and we can say that Abu Talib, may God bless him and grant him peace, stood on the Messenger Muhammad, may God bless him and grant him peace, his heart, his peace, his tenderness, and his Lord. His family, everything he has, his care, his fatherhood, his tenderness, his children, his youth, then his wife, then his house, then a prophet sent by God Almighty until his death, may God bless him and grant him peace.